Légitimité et révolution en Tunisie - Jean-Philippe Bras; Éric Gobe (Revue des Mondes Musulmans et de la Méditerranée)
Abstract : After Ben Ali's departure from power on January 14, 2011, under pressure from popular protest movements, the various actors involved in the Tunisian revolutionary process chose to write a new Constitution and to elect a Constituent National Assembly. In this scenario including the drafting of an electoral law, the High Authority for the Achievement of the Revolution Objectives, Political Reform and Democratic Transition (HIROR) played a fundamental role in the elaboration of the initial legal and political framework of Post-Ben Ali Tunisia. Studying HIROR allows us to understand how Tunisia has gone from the "revolutionary moment", when the people-as-an-event tries to exercise its sovereignty directly in a form of self-government, to institutionalizing change by authorities exercising their power in the name of the people. At the same time, the action of HIROR took place in an unstable scenario marked by the fluidity of the Tunisian revolutionary process, which contributed to weakening the tinkering legitimacy of which it was the bearer.